Effects of fluid restriction on measures of circulatory efficacy in adults with septic shock. Issue 4 (1st February 2017) - Hjortrup, P. B.; Haase, N.; Wetterslev, J.; Lange, T.; Bundgaard, H.; Rasmussen, B. S.; Dey, N.; Wilkman, E.; Christensen, L.; Lodahl, D.; Bestle, M.; Perner, A.
Abstract : Background: The haemodynamic consequences of fluid resuscitation in septic shock have not been fully elucidated. Therefore, we assessed circulatory effects in the first 24 h of restriction of resuscitation fluid as compared to standard care in intensive care unit (ICU) patients with septic shock. Methods: This was a post‐hoc analysis of the multicentre CLASSIC randomised trial in which patients with septic shock, who had received the initial fluid resuscitation, were randomised to a protocol restricting resuscitation fluid or a standard care protocol in nine ICUs. The highest plasma lactate, highest dose of noradrenaline, and the urinary output were recorded in five time frames in the first 24 h after randomisation. We used multiple linear mixed effects models to compare the two groups. Results: We included all 151 randomised patients; the cumulated fluid resuscitation volume in the first 24 h after randomisation was median 500 ml (Interquartile range (IQR) 0–1500) and 1250 ml (500–2500) in the fluid restriction group and standard care group, respectively. The estimated differences in the fluid restriction group vs. the standard care group were 0.1 mM (95% confidence interval −0.7 to 0.9; P = 0.86) for lactate, 0.01 μg/kg/min (−0.02 to 0.05; P = 0.48) for dose of noradrenaline, and −0.1 ml/kg/h (−0.3 to 0.2; P = 0.70) for urinary output during the first 24 h after randomisation. Conclusions: We observed no indications of worsening of measures of circulatory efficacy in the first 24 h of restriction of resuscitation fluid as compared with standard care in adults with septic shock who had received initial resuscitation.